Proinflammatory Cytokine Gene Polymorphisms in Bullous Pemphigoid - Tabatabaei-Panah, Pardis-Sadat; Moravvej, Hamideh; Sadaf, Zahra; Babaei, Hadis; Geranmayeh, Maryam; Hajmanouchehri, Sedigheh; Karimi, Ahmad; Sajjadi, Fatemeh; Arghand, Fereshteh; Ludwig, Ralf J.; Witte, Mareike; Akbarzadeh, Reza (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) is a rare autoimmune skin blistering disease, characterized by the presence of autoantibodies against hemidesmosomal autoantigens. Cytokine expression is altered in BP patients, and several of these differently expressed cytokines, including IL-1α, IL-1, IL-8, and TNF-, contribute to disease pathogenesis. Since genetic polymorphisms in the genes of these cytokines might be implicated in susceptibility to BP disease, we aimed at testing this implication in susceptibility to BP in an Iranian cohort. Blood samples were collected from the subjects and genomic DNA was extracted. To detect the single nucleotide polymorphisms (SNPs), IL-1α (rs1800587), IL-1β (rs1143627, rs16944, rs1143634), IL-8 (rs4073), and TNF-α (rs1799964, rs1800630, rs1799724, and rs361525) genes were genotyped in BP patients and healthy controls as well as IL-8 (rs4073) in pemphigus vulgaris (PV) patients. Quantitative gene expression was evaluated by RT-PCR analysis. A significant difference was observed in the distribution of genotypes or alleles of IL-8 SNP between the BP patients and controls. The A-allele of IL-8 SNP is significantly more prevalent in the control individuals compared to the BP patient. To further validate this observation, we included PV patients as an additional control. Again, the A-allele of IL-8 SNP is significantly more prevalent in the PV compared to the BP patients. While we observed a trend towards significant differences regarding alleles of TNF-α rs1799724 as well as alleles of TNF-α rs1799964, this difference was, however, not evident after correction for multiple analysis. There was no significant difference in all other studied SNPs. In contrast to IL-1α, IL-1β, and TNF-α, IL-8 gene expression levels were significantly higher in the patients than that of controls. The minor allele in IL-8 SNP might play a protective role in susceptibility to BP in Iranian patients. Although higher expression levels of IL-8 gene was found in the patients compared with healthy controls, these levels, however, suggest no association with the examined polymorphism. Moreover, further investigation revealed an elevation in gene expression between wild and polymorphic genotypes of IL-1α rs1800587 and TNF-α rs361525 in the patient group and these SNPs are therefore associated with altering the levels of gene expression.